Extracranial Venous Drainage Patterns in Patients with Multiple Sclerosis and Healthy Controls - McTaggart, R.A. (AJNR Am J Neuroradiol, 2012)
BACKGROUND AND PURPOSE: CCSVI hypothesizes an association between impaired extracranial venous drainage and MS. Published sonographic criteria for CCSVI are controversial, and no MR imaging data exist to support the CCSVI hypothesis. Our purpose was to evaluate possible differences in the extracranial venous drainage of MS and healthy controls using both TOF and contrast-enhanced TRICKS MRV. MATERIALS AND METHODS: Healthy subjects (n = 20) and patients with MS (n = 19) underwent axial 2D-TOF neck MRV (to assess flattening) and TRICKS MRV (to assess collaterals) at 3T. Two neuroradiologists blinded to cohort status scored IJV flattening and the severity of non-IJV collaterals by using a 4-point qualitative scale (normal = 0, mild = 1, moderate = 2, severe = 3). κ was used to assess reader agreement. Comparisons between groups were performed by using the Wilcoxon rank sum test. The Spearman rank correlation was used to assess the relationship between IJV flattening and collateral scores and, in patients with MS, EDSS scores. RESULTS: The 2 groups were matched for age and sex (MS, 45 ± 8 years, 79% female; healthy controls, 47 ± 10 years, 65% female). Reader agreement for IJV flattening and collateral severity was good (κ = 0.74) and moderate (κ = 0.58), respectively. While IJV flattening was seen in both patients with MS and healthy controls, scores for the patients with MS were significantly higher (P = .002). Despite a trend, there was no significant difference in collateral scores between groups (P = .063). There was a significant positive correlation between flattening and collateral scores (ρ = 0.32, P = .005) and EDSS and flattening scores (ρ = 0.45, P = .004) but not between EDSS and collateral scores (ρ = 0.01, P = .97). CONCLUSIONS: These results indicate that patients with MS have greater IJV flattening and a trend toward more non-IJV collaterals than healthy subjects. The role that this finding plays in the pathogenesis or progression of MS, if any, requires further study.